Teoria de campo de corda bosônica e considerações sobre possíveis extensões - Granado, Diego Rocha (2021)
Submitted by Boris Flegr (boris@uerj.br) on 2021-01-06T21:13:44Z No. of bitstreams: 1 DissertacaoDiegoRochaGranado.pdf: 1023635 bytes, checksum: 53b81f357db245bb14d41839d83399d7 (MD5)